The Power Of Personalization : Exploring The Impact Of Ai-Driven Marketing Strategies On Consumer Loyalty In E-Commerce - Zed, Etty Zuliawati; Tri Mulyani Kartini; Pupung Purnamasari (SEAN Institute, 2024)
This study investigates the impact of AI-driven personalization on consumer loyalty within the e-commerce sector. With the growing adoption of artificial intelligence, e-commerce platforms increasingly rely on personalization strategies—such as tailored product recommendations, targeted advertising, and dynamic website customization—to enhance user experience and foster consumer loyalty. Data were collected from a sample of online shoppers and analyzed through validity, reliability, correlation, and regression tests. The results reveal a significant positive relationship between AI-driven personalization and consumer loyalty, supporting the idea that personalized experiences enhance repurchase intentions, brand advocacy, and emotional connection. The study contributes to existing literature by providing empirical evidence on the effectiveness of AI personalization in building loyalty, underscoring the importance of understanding consumer demographics for targeted personalization strategies. Practical implications suggest that e-commerce platforms can benefit from personalized marketing approaches, although careful attention to privacy and transparency remains essential. Limitations and directions for future research are discussed, particularly the need for longitudinal studies and cross-cultural examinations to validate these findings across diverse consumer groups.